Ally, friend, or mentor? Creating and maintaining effective cross-class alliances. Issue 4 (1st October 2016) - Lawless, Brandi
ABSTRACT: This essay (re)examines the notion of intercultural alliances in one U.S. nonprofit organization trying to end poverty. The nonprofit, referred to as Transforming Poverty Partnerships, has built their program around building relationships between people in poverty and middle-class "Allies." This analysis reveals a number of problematic themes that emerge from previous conceptions of cross-class alliances and implications for improving such alliances within various contexts.